PELAKSANAAN AKAD MUDHARABAH DI BMT TUMANG SURAKARTA: ANALISA FATWA DSN-MUI NO.07/DSN-MUI/IV/2000 TENTANG PEMBIAYAAN MUDHARABAH - Sumadi Sumadi; Suprihati Suprihati; Eko Verdianto (Indonesian Journal of Shariah and Justice, 2021)
This study aims to determine the implementation of the Mudharabah Agreement at BMT Tumang Surakarta in accordance with the DSN-MUIfatwa no. 07/DSN-MUI/IV/2000 or not. This research was conducted at BMT Tumang Surakarta. The data analysis technique in this study useda descriptive analysis method using a qualitative approach. The results showed that the implementation of Mudharabah financing at BMTTumang was not fully in accordance with the Fatwa of DSN N0:07/DSN-MUI/IV/2000. Things that are not in accordance with DSN FatwaN0:07/DSN-MUI/IV/2000, namely if the mudharib suffers an unintentional loss, the loss should be borne by BMT Tumang, but BMT Tumang cannot bear the loss, if there is a loss, the mudharib is asked to return the principal only. But if mudharib still can't afford it then BMT Tumang is forced to disburse the guarantee. 2) The actual guarantee can only be disbursed for the mudharib who is proven to have committed an intentional mistake, but at BMT Tumang the guarantee will also be disbursed when the mudharib suffers a loss who has been given relief to pay the principal but still cannot carry out the deposit, then BMT Tumang will be forced to withdraw the guarantee.